Analyzing the use of illocutionary and perlocutionary acts of ‘Dilan’ in an Indonesian teen novel - Ika Apriani Fata; Yunisrina Qismullah Yusuf; Naziratun Ulfa; Hilda Delavari (English Education Journal, 2022)
This study aims to analyze the speech acts based on Searle’s classification of illocutionary acts and perlocutionary acts in the teen novel, ‘Dilan, Dia adalah Dilanku Tahun 1990’. This research aims to identify and describe these acts as done by one of the main characters, Dilan. This research used a qualitative method. The data were in the form of a description where all of Dilan’s utterances are identified in the novel and further analyzed. The findings of this research showed that there are five types of illocutionary acts in the novel. They are assertive, directive, commisive, expressive, and declarative. The assertive type is the dominant type used by Dilan rather than the other types. In terms of the perlocutionary act, the effect of Dilan’s utterances tends to persuade his hearers, impress, encourage, convince, amuse, intimidate, inform and surprise them. As a consequence, persuading the hearers is the dominant effect based on Dilan’s utterances. The context of situation determined all the acts performed by this main character. Conclusively, the findings of this study are expected to broaden the context of linguistics, especially of speech acts as a part of pragmatics in linguistics.